Eco-friendly management of brinjal collar rot caused by Sclerotium rolfsii Sacc. - JADON*, KULDEEP SINGH (Indian Phytopathology, 2009)
The pathogen associated with collar rot of brinjal was identified as Sclerotium rolfsii (Sacc.). The present investigation was carried out for ecofriendly management of the disease, it includes various practices i.e. summer ploughing, soil solarization, biocontrol agents, green manuring and soil amendments. The soil and seedling dip treatment with Trichoderma viride (T5 ) @ 4g/kg of seedling and 50mg with 5 g FYM/m2 respectively was found most effective in reducing the per cent disease incidence followed by summer ploughing.